The morphological impact of municipal planning instruments on urban agriculture - Mélice Dias, Ana (2020)
With the growth of urban population, humanity faces new challenges concerning urban food provision. Urban planning is paramount to guarantee a sustainable functioning of the several systems which operate within the urban realm, including the food system. However, while it is widely acknowledged that urban planning would benefit from the integration of urban agriculture, which operates at the production stage of the food system, it is less clear what are the morphological impacts of planning instruments on urban space, in terms of urban agriculture. This paper tries to address this gap, while focusing on one particular area of Portugal, Lisbon and its surrounding territory (Lisbon’s Greater Area). The proposed methodological approach aims to trace the perception of urban agriculture by municipal planning instruments (Municipal Master Plans) and identify their impact in contemporary urban agriculture solutions. It concludes that current planning regulations in Lisbon’s Greater Area are specifically focused on morphological solutions that give preference to urban agriculture uses related to leisure and aesthetic solutions, in determinant of design solutions that tackle economic growth or ecological diversity.